Development of Interactive E-Modules to Increase Learning Motivation and Science Literacy in Elementary School Students - Christina Ismaniati; Baroroh Iskhamdhanah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The article aimed to produce interactive e-modules from my country that meets the qualified criteria and to know the effectiveness of the interactive e-modules of my country produced to improve the learning motivation and science literacy of elementary school students of grade IV in the nearby. The research used research and development (R&D), with ADDIE model. The subject of a pilot project for a small group trial consists of 15 students and 1teacher in SD Negeri Soka. Next, the test subject of the field trial consists of 20 Muhammadiyah Kalinampu 1 students as a control class and 20 students IV grade SD Muhammadiyah Kalipakem 1 as an experimental class. Collecting data used interview guide, observation guidelines, product assessment sheet, teacher-response scale, student response scale, and the motivational scale of study and science literary test. The results showed that: (1) the resulting interactive e-module met the criteria of